Kinerja Tenaga Pendamping Desa Dalam Pembangunan Desa Di Kabupaten Bungo Provinsi Jambi (Studi Di Desa Koto Jayo Dan Desa Tanah Tumbuh Kecamatan Tanah Tumbuh) - Muhammad Adriansah; Ika Sartika; Andi Ony (UIR Press, 2022)
The task of village assistants in assisting village development has not run optimally. If this happens continuously, it will affect the village development process as mandated in Law Number 6 of 2014 concerning Villages. The research method used in order to review, develop and test the truth to find a scientific knowledge. The methods that can be used are very diverse, of course the method to be chosen must be appropriate and closely related to the procedures, tools and research design that will be carried out by the researcher. While the research method is basically a scientific way to obtain data with certain purposes and uses. There are four keywords that need to be considered, namely, scientific method, data, purpose and usability. The scientific method means research activities based on scientific characteristics, namely rational, empirical, and systematic. Rational means that research activities are carried out in ways that make sense, so that they are affordable by human reasoning. Empirical means that the methods used can be observed by humans, so that other people can observe and know the methods used. Systematic means that the process used in the research uses certain logistical steps. The results showed that Tanah Grow District was measured by how the innovation model was applied, the innovation process and the benefits of innovation there was no initiative from village assistants because of the limited authority in implementing assistance in villages as regulated in the Regulation of the Minister of Villages PDTT Number 19 of 2020 concerning Guidelines General Village Community Assistance. The conclusions that can be drawn from the results of the discussion and research are as follows: Village assistants in village development in Koto Jayo Village, Tanah Grow District, Bungo Regency, Jambi Province, can guarantee that village performance has not met all indicators, only a few indicators, quality of work (Quality of Work) Work) villages that are assessed to meet the indicators, because every month village assistance must submit individual reports.